Drivers of Landscape Changes in Coastal Ecosystems on the Yukon-Kuskokwim Delta, Alaska - M. Torre Jorgenson; Gerald V. Frost; Dorte Dissing (Remote Sensing, 2018)
The Yukon-Kuskokwim Delta (YKD) is the largest delta in western North America and its productive coastal ecosystems support globally significant populations of breeding birds and a large indigenous population. To quantify past landscape changes as a guide to assessing future climate impacts to the YKD and how indigenous society may adapt to change, we photo-interpreted ecotypes at 600 points within 12 grids in a 2118 km2 area along the central YKD coast using a time-series of air photos from 1948–1955 and 1980 and satellite images from 2007–2008 (IKONOS) and 2013–2016 (WorldView). We found that ecotype classes changed 16.2% (342 km2) overall during the ~62 years. Ecotypes changed 6.0% during 1953–1980, 7.2% during 1980–2007 and 3.8% during 2007–2015. Lowland Moist Birch-Ericaceous Low Scrub (−5.0%) and Coastal Saline Flat Barrens (−2.3%) showed the greatest decreases in area, while Lowland Water Sedge Meadow (+1.7%) and Lacustrine Marestail Marsh (+1.3%) showed the largest increases. Dominant processes affecting change were permafrost degradation (5.3%), channel erosion (3.0%), channel deposition (2.2%), vegetation colonization (2.3%) and lake drainage (1.5%), while sedimentation, water-level fluctuations, permafrost aggradation and shoreline paludification each affected <0.5% of the area. Rates of change increased dramatically in the late interval for permafrost degradation (from 0.06 to 0.26%/year) and vegetation colonization (from 0.03 to 0.16%/year), while there was a small decrease in channel deposition (from 0.05 to 0.0%/year) due largely to barren mudflats being colonized by vegetation. In contrast, rates of channel erosion remained fairly constant. The increased permafrost degradation coincided with increasing storm frequency and air temperatures. We attribute increased permafrost degradation and vegetation colonization during the recent interval mostly to the effects of a large storm in 2005, which caused extensive salt-kill of vegetation along the margins of permafrost plateaus and burial of ...